ASPIRE - A Journey from Intuition to Innovation - Alhad Mulkalwar (University Library System, University of Pittsburgh, 2022)
The idea of academic research is perceived by many students as interesting, but what stops them from actually indulging in it, is a simple question, 'How does one start?' Those who do start seldom remain with the project till the end and very few eventually co-author the publication. This attrition could be fuelled by numerous factors including lack of right mentorship, conflict with academics, or simply a loss of interest. There was a need to practice and teach research from the perspective of an undergraduate and hence inculcate the culture of Research and Evidence-Based Medicine into medical education. As a solution to this predicament, a student-led research council named, 'A.S.P.I.R.E: Association for Support and Propagation of Innovation, Research & Education' was formed. Its activities were focused on building a peer-based research environment to learn via module-wise teaching and mentoring sessions and a practical approach to inculcate the culture of evidence-based medicine in young professionals via Journal club sessions. This article summarizes the author's experience of implementing this idea and the hurdles and barriers he faced in the process. The author also provides a reflection on this journey which provided him with innumerable lessons and positive takeaways.